PENGARUH KUALITAS PELAYANAN DAN KEPUASAN MAHASISWA TERHADAP INTENSI MEREGISTRASI ULANG MAHASISWA - Sylvana, Andi (Jurnal Organisasi dan Manajemen, 2006)
This article is written based on the research about the influance of service quality and student?s satisfaction toward the intensity of student?s re-registration. This research is a replica of Davidow?s research regarding timeliness, apology, redress, facilitation, credibility and attentiveness as an indicator of service quality that could influence the satisfaction as well as the intention to repurchase. The analisys method that?s being used in this research is the hierarchy analisys method. By using this analisys, the causal relation between variable and the hierarchy of each variables, whether direct or indirect relations, can be estimated. The population of this research is the student of UT in UPBJJ all over Indonesia. The result of this research indicates that service quality?s factor has a significant influence toward the student?s satisfaction; student satisfaction?s factor has a significant influence toward the intensity of student?s re-registration; service quality factor has a significant influence toward the intensity of student?s re-registration; both service quality and student satisfaction?s factor don?t have a significant influence toward the intensity of student?s re-registration.